Label-free technique for universal and sequence independent detection of oligonucleotides and nuclease activity - Gooran, Negin; Borsa, Baris A; Hernandez, Frank J; Härmä, Harri; Kopra, Kari (Oxford University Press, 2026)
Nucleases are a diverse group of enzymes cleaving phosphodiester bonds of deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) with varying specificity. Depending on the context, nucleases can be considered as unwanted contaminants, molecular biology tools, drug targets, or diagnostic markers. Current methods for nuclease activity monitoring are mainly based on fluorescence detection, by using either labeled substrates or oligonucleotide-binding dyes. These methods are often limited to single- and double-stranded DNA or RNA or the determination of either endo- or exonuclease activity. Universal, simple, and sensitive nucleotide sequence and modification-independent methods, enabling endo- and exonuclease activity monitoring, are not currently available. To address this, we have developed the NucleoProbe technique, as a label-free and substrate-independent option for high-sensitivity endo- or exonuclease activity monitoring. External peptide-probe-based detection utilizing time-resolved luminescence readout enables low nanomolar sensitivity for DNA and RNA oligonucleotides down to 9 nt in length. We also demonstrate the universality by monitoring both endo- and exonuclease activity, with over five-fold improved sensitivity in comparison to our commercial standard assay. Additionally, we show the further potential of the method by specifically detecting S. aureus via its specific micrococcal nuclease activity and, finally, by monitoring nuclease activity from spiked urine.